Grain boundary diffusion driven spark plasma sintering of nanocrystalline zirconia - Borodianska, Hanna (2013)
A methodology is proposed to investigate in detail shrinkage kinetics under isothermal spark plasma sintering (SPS) conditions applied to ceramic nano powders such as Y2O3 stabilized ZrO2. To do so, mild SPS conditions were used (low temperatures and pressure, long dwell times). The extracted experimental activation energy has the value of 246 ± 37 kJ mol−1 and the slope of the curves on the intense densification stage is around 0.33. Results are in agreement with densification by a grain-boundary diffusion mechanism as for conventional sintering and the contribution from the specific pressure-assisted mechanisms as for hot pressing is insignificant. This result suggests that exploration of mild SPS might prove rewarding in separation and control of the sintering mechanisms leading to production of specific ceramic with new or improved functionality.